Intratumoral microbiota omics analysis in head and neck squamous cell carcinoma - Xie, Cuiliu; Yan, Qifang; Zhang, Pan; Zhang, Li; Yan, Guowei (Frontiers in Microbiology, 2025)
ObjectiveThe intratumoral microbiota plays a critical role in the progression of head and neck squamous cell carcinoma (HNSCC). This study aimed to comprehensively characterize the intratumoral microbiota in HNSCC and investigate its potential associations with tumor progression and host metabolic functions using a 4-nitroquinoline 1-oxide (4NQO)-induced murine model.MethodsA HNSCC mouse model was established through administration of 4NQO in drinking water. Histopathological and IHC analyses were performed to confirm tumor development and proliferative activity. The microbial composition of tumor and normal tissues was assessed using 5R 16S rDNA gene sequencing.ResultsSuccessful induction of HNSCC was confirmed by histopathology and elevated PCNA expression. Significant decreases in microbial α-diversity and altered β-diversity were observed in tumor tissues. Enrichment of genera such as Aggregatibacter and Pseudomonas, and depletion of Lactobacillus and Acinetobacter, were characteristic of the intratumoral microbiota. RDA and linear regression revealed a significant correlation between the intratumoral microbiota and PCNA expression. Predictive functional analysis indicated alterations in metabolic pathways, including fatty acid biosynthesis and nucleotide metabolism, in the tumor microenvironment.ConclusionThese findings demonstrate that intratumoral microbiota dysbiosis is closely associated with HNSCC progression. The study establishes a foundational murine model for further mechanistic research and suggests the potential of the intratumoral microbiota as a biomarker or therapeutic target in HNSCC.